Value Added Processing of Plantation Products to Increase Farmers' Income and Welfare - Sakti Sakti; Siti Maulidina (Jurnal PKM Manajemen Bisnis, 2023)
One of the keys to business success is creativity and innovation, but both can only be achieved through continuous learning. As in the village of Cilebud Bogor, the abundance of guava fruit plantations, not many farmers have developed it into value-added products. Generally, the harvest, directly sold in the form of fruit only. This requires a role from many parties, one of which is the academic community, to provide provision of knowledge about the processing of high economic value plantation products. To answer this goal, community service activities were carried out by students and lecturers at Pasundan University in the village of Cilebud, Bogor. This service activity is in the form of training in making juice and dodol from guava fruit, as a strategy to increase farmers' income. The number of participants who took part in this activity were 32 people, consisting of farmers, sellers and people around the village of Cilebud. The results of the activity showed that the community was enthusiastic about the practice of making juice and lunkhead from processed guava. Apart from that, they also taught how to pack and digitally market, so that processed products can be widely known by Indonesian people, especially tourists who visit the city of Bogor.